1975
DOI: 10.1002/chin.197541232
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A NOVEL CLASS OF POTENTIAL ANTIDEPRESSANTS. 1‐AMINOALKYL‐1,3,4,9‐TETRAHYDROPYRANO(3,4‐B)INDOLES

Abstract: Aus den Indol‐äthanolen (I) werden mit Acetessigester (II) die Heterocyclen (III) gewonnen, die zu den Derivaten (IV) methyliert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…gave 66% of the product 43 as an oil: NMR 1.30 [3, s, (C)3CCH3], 3.55 (3, s, OCH3), 8.10 (1, broad, NH). Elution with CgHe-MegGO (4:1) gave 15% of the corresponding acid 44. l-Methyl-l,2,3,4-tetrahydrocarbazole-l-propionic Acid (14). A solution of the pyridocarbazolone 10 (0.5 g, 0.002 mol) in EtOH (10 ml) and 10% aqueous NaOH (2 ml) was heated at reflux for 3 h. The EtOH was removed in vacuo and H20 was added.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…gave 66% of the product 43 as an oil: NMR 1.30 [3, s, (C)3CCH3], 3.55 (3, s, OCH3), 8.10 (1, broad, NH). Elution with CgHe-MegGO (4:1) gave 15% of the corresponding acid 44. l-Methyl-l,2,3,4-tetrahydrocarbazole-l-propionic Acid (14). A solution of the pyridocarbazolone 10 (0.5 g, 0.002 mol) in EtOH (10 ml) and 10% aqueous NaOH (2 ml) was heated at reflux for 3 h. The EtOH was removed in vacuo and H20 was added.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies from our laboratories have shown that 9-ethyl-IV, N, 1-trimethyl-1,2,3,4-tetrahydrothiopyrano- [3,4-¿>]indole-l-ethanamine hydrochloride (2, tandamine hydrochloride, USAN) is a potent antidepressant as demonstrated in various models,10"13 including prevention of reserpine-induced ptosis.10,12 An oxygen analogue, IV,iV,l,9-tetramethyl-1,2,3,4-tetrahydropyrano [3,4-¿>]indole-1-ethanamine hydrochloride (3,, has also been found to have potential antidepressant properties as reflected by its activity in the reserpine ptosis test. 14 In contrast to the tetrahydrocarbazoles cited above,2"9 compounds 2 and 3 possess, apart from their novel nuclei, dimethylaminoethyl groups at position 1 as well as alkyl groups at the 1 and 9 positions. Studies of numerous analogues of 2 and 3 have indicated that their antidepressant-like properties are associated with these structural features.12" 14 We have now investigated the effects of replacing the dihydrothiopyrano and dihydropyrano rings of 2 and 3 with partially saturated carbocyclic systems, and the present report describes the synthesis and biological evaluation of a series of cycloalkanoindoles having substitution patterns found to be relevant for the antidepressant-like properties of 2 and 3.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The introduction of the 8-ethyl group, to generate etodolac, results in a tenfold enhancement of activity, and as the bulk of the 8-alkyl group increases, activity markedly diminishes. 6,11 8/7,8 Inspection of the results shown in Table I1 on 5,8-and 7,8-disubstituted derivatives shows that 5,g-dimethyl and 5,B-dichloro derivatives, as well as 7,8-dichloro and 7-1riethyl-8-chloro derivatives, are not substantially more active than the corresponding 8-monosubstituted derivatives; in contrast, both 7-fluoro-8-methyl and 7-chloro-&methyl derivatives are 5-7 times more potent than the correspondi:ng 8-monosubstituted derivatives. l1…”
Section: Position-7mentioning
confidence: 98%